The epidemiology of non-viral gastroenteritis in New Zealand children from 1997 to 2015: an observational study - Emma Jeffs; Jonathan Williman; Natalie Martin; Cheryl Brunton; Tony Walls (BMC, 2019)
Abstract Background Acute gastroenteritis is a substantial cause of hospitalization in children. Shigella, Salmonella, Campylobacter, Yersinia, enterotoxigenic Escherichia coli (ETEC), Giardia and Cryptosporidium are gastrointestinal pathogens that are notifiable in New Zealand (NZ). The impact of these infections in the pediatric population has not yet been analyzed. The aim of this study was to describe the epidemiological trends in disease notifications and hospital admissions due to non-viral gastroenteritis in NZ children. Methods In this population-based descriptive study, age-specific and age-standardized notification and hospital admission rates were analyzed from 1997-to-2015 for Shigella, Salmonella, Campylobacter, Yersinia, ETEC, Giardia and Cryptosporidium infections in children < 15 years of age. Variations in disease by gender, age, ethnicity and geography were described. Results From 1997-to-2015 there were 74,454 notifications (57.6% male) and 3192 hospitalizations (56.4% male) due to non-viral gastroenteritis in NZ children aged < 15 years. There was an overall trend towards a reduction in disease notifications and hospitalizations, however each disease showed a unique pattern of change over time. Campylobacter was the pathogen most frequently notified, accounting for 51.7% of notifications and 43.4% of hospitalizations. The hospitalization-to-notification ratios were, from highest to lowest, Salmonella typhi (1:1.09), Shigella (1:4.0), ETEC (1:7.81), nontyphoidal Salmonella (1:13.1), Campylobacter (1:27.8), Yersinia (1:29.2), Cryptosporidium (1,33.4), and Giardia (1,72.5). Compared to females, male notification rates were approximately 40% higher for Campylobacter, 25% higher for Giardia and Yersinia, and 15% higher for Cryptosporidium and nontyphoidal Salmonella (p < 0.001). Notification rates were highest in children 1-4 years, with the exceptions of nontyphoidal Salmonella, Salmonella typhi and Yersinia. Notification rates for nontyphoidal Salmonella and Yersinia were highest in children < 1 year, and for Salmonella typhi those aged 5-9 years. Children < 1 year were most likely to be hospitalized. Conclusions The incidence of non-viral gastroenteritis in NZ children reduced during the 19-year period considered. The burden of disease was highest in the community, with only a small percentage of cases requiring hospitalization. This study provides important insight into the non-viral causes of gastroenteritis in NZ children and how environmental influences and changes in food safety practices may have helped to reduce the burden of these diseases in children.